Habituation of the stress response multiplex to repeated cold pressor exposure - Bullock, Tom; MacLean, Mary H.; Santander, Tyler; Boone, Alexander P.; Babenko, Viktoriya; Dundon, Neil M.; Stuber, Alexander; Jimmons, Liann; Raymer, Jamie; Okafor, Gold N.; Miller, Michael B.; Giesbrecht, Barry; et al. (Frontiers in Physiology, 2023)
Humans show remarkable habituation to aversive events as reflected by changes of both subjective report and objective measures of stress. Although much experimental human research focuses on the effects of stress, relatively little is known about the cascade of physiological and neural re-sponses that contribute to stress habituation. The cold pressor test (CPT) is a common method for inducing acute stress in human participants in the laboratory; however, there are gaps in our under-standing of the global state changes resulting from this stress-induction technique and how these responses change over multiple exposures. Here, we measure the stress response to repeated CPT exposures using an extensive suite of physiologic measures and state-of-the-art analysis tech-niques. In two separate sessions on different days, participants underwent five 90 s CPT expo-sures of both feet and five warm water exposure, while electrocardiography (ECG), impedance cardiography, continuous blood pressure, pupillometry, scalp electroencephalography (EEG), sali-vary cortisol and self-reported pain assessments were recorded. A diverse array of adaptive re-sponses are reported that vary in their temporal dynamics within each exposure as well as habitua-tion across repeated exposures. During cold-water exposure there was a cascade of changes across several cardiovascular measures (elevated heart rate (HR), cardiac output (CO) and MAP and re-duced left-ventricular ejection time (LVET) and HF). High-frequency heart-rate variability (HF) also increased in anticipation of cold-water. Increased pupil dilation was observed, as was in-creased power in low-frequency bands (delta and theta frequency bands) across frontal EEG elec-trode sites. Several cardiovascular measures also habituated over repeated cold-water exposures (HR, MAP, CO) as did pupil dilation and alpha frequency activity across the scalp. Anticipation of cold-water induced stress effects in the time-period immediately prior to exposure, indexed by increased pupil size and cortical disinhibition in the alpha and beta frequency bands across central scalp sites. These results provide comprehensive insight into the evolution of a diverse array of stress responses to an acute noxious stressor, and how these responses adaptively contribute to stress habituation.